The tender bar : a memoir - Moehringer, J. R., 1964- (Hachette Books, an imprint of Perseus Books, LLC, 2021)
"J.R. Moehringer grew up captivated by a voice. It was the voice of his father, a New York City disc jockey who vanished before J.R. spoke his first word. Sitting on the stoop, pressing an ear to the radio, J.R. would strain to hear in that plummy baritone the secrets of masculinity and identity. Though J.R.'s mother was his world, his rock, he craved something more, something faintly and hauntingly audible only in The Voice. At eight years old, suddenly unable to find The Voice on the radio, J.R. turned in desperation to the bar on the corner, where he found a rousing chorus of new voices. The alphas along the bar--including J.R.'s Uncle Charlie, a Humphrey Bogart look-alike; Colt, a Yogi Bear sound-alike; and Joey D, a softhearted brawler--took J.R. to the beach, to ballgames, and ultimately into their circle. They taught J.R., tended him, and provided a kind of fathering-by-committee. Torn between the stirring example of his mother and the lurid romance of the bar, J.R. tried to forge a self somewhere in the center. But when it was time for J.R. to leave home, the bar became an increasingly seductive sanctuary, a place to return and regroup during his picaresque journeys. Time and again the bar offered shelter from failure, rejection, heartbreak--and eventually from reality."--Amazon.